Application of a co-adsorption model for the design of CIL/CIP circuits. Issue 1 (2nd January 2020) - Bax, A.R.; Wardell-Johnson, G.M.; Staunton, W.P.
ABSTRACT: One of the main problems in the design of carbon adsorption circuits for the processing of high silver gold ores is that the commonly used gold adsorption models are unable to replicate the frequently observed displacement of silver on carbon by gold in the first contactors of carbon-in-pulp/carbon-in-leach (CIP/CIL) trains operating with high metal loadings on carbon and high silver gold ratios. A model has been developed by Curtin University's Gold Technology Group to simulate the competitive co-adsorption of gold and silver by activated carbon. The model utilises multi-component equilibrium isotherms and film-diffusion rate equations to describe the adsorption of gold and silver onto activated carbon. The model has been validated using laboratory and plant data. Case studies are presented to demonstrate the application of the model for the design of a greenfield project processing a gold/silver ore.